Reviewing Critical Discourse Analysis (CDA) Studies: Ideas from Chinese Scholars - Zhan Li Xia; Budianto Hamuddin (REiLA : Journal of Research and Innovation in Language, 2019)
This present study discuss Critical Discourse Analysis (CDA) studies made by chinese scholars. The rising of the studies in china seems started at the beginning at 90s’. It is almost two decades since chinese scholars get involved in Critical Discourse Analysis research. In short time the scholars showing their ability in critical discourse analysis by publishing many papers since it. This present library research aims at reviewing the CDA studies since 1990 until present day to see the related link between discourse, control and ideology in relation between personal, facts, and social-cultural development in. The studies starts with several definitions, origin and some leading research in Europe and America of Critical Discourse Analysis. This present study reveals that the papers producd by chinese scholars on CDA fields since 1990s somehow mostly discuss in the area of linguistics, political, philosophy, media studies, methodological, and theoretical studies expression. The Chinese scholars are floundered to produce Critical Discourse Analysis studies with unique research to study without limits. Recently the research shows that CDA has been applied to the investigation of varied discourses context to disclose social reality, focusing on the inter-relationship between discourse, power and ideology.